The Effect of Inflation, Unemployment, and GRDP on the Number of Poor People in South Sumatra Province - Ayu Geby Gisela Syaputri; Muhammad Bahrul Ulum; Ummi Kalsum; Primasari Fitria (Jurnal Ilmiah Ekonomi Global Masa Kini, 2026)
This study aims to analyze the effects of inflation, unemployment, and Gross Regional Domestic Product (GRDP) on the number of poor people in South Sumatra Province during the 2015–2023 period. Poverty remains one of the economic problems that continues to be a major concern for the regional government because it is directly related to community welfare. A high inflation rate can reduce people’s purchasing power, and increased unemployment can decrease community income, while GRDP growth is expected to improve economic activities and public welfare. Therefore, this study was conducted to determine the relationship between these macroeconomic variables and the number of poor people. This study uses a quantitative approach with secondary data obtained from Statistics Indonesia (BPS) and official regional government publications during a certain period. The analytical method used is multiple linear regression analysis to determine the partial and simultaneous effects of inflation, unemployment, and GRDP on the number of poor people in South Sumatra. The results of the study indicate that unemployment has a positive and significant effect on the number of poor people, while inflation and GRDP have a negative and insignificant effect on the number of poor people. Simultaneously, these three variables have a significant effect on the poverty level in South Sumatra. This study is expected to serve as a consideration for the government in formulating economic policies oriented toward poverty reduction and improving community welfare. Keywords: Poverty, Inflation, Unemployment, GRDP